2012
DOI: 10.1155/2012/672403
|View full text |Cite
|
Sign up to set email alerts
|

Normative Data for Bone Mass in Healthy Term Infants from Birth to 1 Year of Age

Abstract: For over 2 decades, dual-energy X-ray absorptiometry (DXA) has been the gold standard for estimating bone mineral density (BMD) and facture risk in adults. More recently DXA has been used to evaluate BMD in pediatrics. However, BMD is usually assessed against reference data for which none currently exists in infancy. A prospective study was conducted to assess bone mass of term infants (37 to 42 weeks of gestation), weight appropriate for gestational age, and born to healthy mothers. The group consisted of 33 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 39 publications
3
16
0
Order By: Relevance
“…Infants were scanned in array mode to obtain BMC of the whole body, lumbar spine vertebrae 1 to 4, and whole femur while sleeping (nonsedated) as previously described. 10,22 Change in BMC was calculated between visits. The co-efficient of variation was 1% for BMC and 0.3% for BMD using a spine phantom (Hologic phantom No.…”
Section: Secondary Efficacy Outcomesmentioning
confidence: 99%
“…Infants were scanned in array mode to obtain BMC of the whole body, lumbar spine vertebrae 1 to 4, and whole femur while sleeping (nonsedated) as previously described. 10,22 Change in BMC was calculated between visits. The co-efficient of variation was 1% for BMC and 0.3% for BMD using a spine phantom (Hologic phantom No.…”
Section: Secondary Efficacy Outcomesmentioning
confidence: 99%
“…[IOM] 2010). Across the lifespan, the most accelerated rates of growth and bone mineral accretion occur in infancy (Gallo et al 2012), with evidence indicating that maximising bone accretion during this time benefits bone health at later stages of the life cycle (Cooper et al 2002;Gallo et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, there are limitations to when this method should be applied in forensic contexts. For example, research has shown that the relationship between bone volume and bone area in juveniles varies between growth stages 12,92 . Ensuring that the proper methodology and normative data is being used (i.e., age-matched normative data) is imperative.…”
Section: Discussionmentioning
confidence: 99%